Strict Surgical Repair for Bile Leakage Following the Roux-en-Y Hepaticojejunostomy - Zhang, Keying; Wu, Linfeng; Gao, Kai; Yan, Chengwei; Zheng, Chao; Guo, Chunbao (Frontiers in Surgery, 2021)
Background: The optimal bile leakage management strategy in the pediatric population following the initial Roux-en-Y hepaticojejunostomy is still a matter of discussion today. Here, we assessed the roles of bile leakage management and surgical implementation on outcomes for patients with bile leakage. Materials and methods: A revised protocol for bile leakage management with restricted surgical intervention was implemented at Chongqing Children’s Hospital on March 15, 2013 and Sanxia Hospital on April 20, 2013. We performed a retrospective, historical control analysis for the protocol implementation to compare the short- and long-term outcomes using the corresponding statistical methods. Results There was a total of 84 patients included in the analysis, including 46 patients in the pre-protocol group and 38 patients in the post-protocol group. No statistical differences for the demographic features were found between the two groups. There was a decrease in redo surgeries in the post-protocol cohort compared to those in the pre-protocol cohort (odds ratio [OR]=4.48 [95% CI, 1.57-12.77]; p=0.003). Furthermore, patients in the post-protocol group were less likely to be associated with intensive care unit(ICU) admission (OR=3.72 [95% CI, 1.11-12.49]; p=0.024) compared to patients in the pre-protocol group, respectively. There was no mortality between the two groups. Conclusions: A restrictive surgical intervention strategy can effectively reduce the rate of redo surgery and exhibited promising outcomes for bile leakage in terms of postoperative recovery and hospitalization costs.